Enhancing Mathematics Learning Outcomes of First-Grade Students through the STAD Cooperative Learning Model: A Classroom Action Research at a public primary school in Klaten, Indonesia - Indarwati, Dewi; Kusumaningtyas, Dian Artha; Rumgayatri (The Indonesian Institute of Science and Technology Research, 2024)
This study aims to investigate the enhancement of mathematics learning outcomes through the implementation of the STAD cooperative learning model. Employing a classroom action research approach, the study unfolds across two cycles. The subjects consist of 29 first-grade students, comprising 10 male and 19 female students. Data collection techniques encompass observation, tests, and documentation, facilitated by observation sheets and written tests as research instruments. Data analysis involves both qualitative and quantitative descriptive analysis. Results indicate that the utilization of the STAD cooperative learning model significantly improves students' mathematics learning outcomes. This improvement is evidenced by the progressive increase in the class's average test scores across each cycle, with average scores rising from 54.48 in the pre-cycle to 70.52 in cycle I and further to 82.6 in cycle II.